2020
DOI: 10.1111/trf.15729
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and ferritin testing to mitigate iron depletion in male plateletpheresis donors

Abstract: BACKGROUND Most single‐donor platelet (SDP) donors transition to plateletpheresis after prior red blood cell (RBC) donation. Recruitment may follow identification of a high platelet count, a marker associated with iron depletion (ID). SDP donors may have underrecognized risk for iron depletion. STUDY DESIGN AND METHODS To assess the prevalence of ID, we performed ferritin testing on male plateletpheresis donors with hemoglobin levels less than 13.5 g/dL. Multivariable logistic regression identified risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recent studies examined iron status relating to apheresis collection of platelets, plasma, or double red cells. A United States study of male plateletpheresis donors with low-normal hemoglobin found high prevalence of iron deficiency and a clear dose–response association with plateletpheresis donation count [25]. In contrast, a study of plasma donors found that iron deficiency was rare and not more common in high-frequency donors [26].…”
Section: Prevalence Of Iron Deficiency In Blood Donorsmentioning
confidence: 99%
“…Recent studies examined iron status relating to apheresis collection of platelets, plasma, or double red cells. A United States study of male plateletpheresis donors with low-normal hemoglobin found high prevalence of iron deficiency and a clear dose–response association with plateletpheresis donation count [25]. In contrast, a study of plasma donors found that iron deficiency was rare and not more common in high-frequency donors [26].…”
Section: Prevalence Of Iron Deficiency In Blood Donorsmentioning
confidence: 99%